2007
DOI: 10.1111/j.1399-6576.2006.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of regurgitation and pulmonary aspiration of gastric contents in survivors from out‐of‐hospital cardiac arrest

Abstract: Although there was a strong association between clinical regurgitation and radiological findings consistent with aspiration, our data suggest that regurgitation is not invariably followed by radiological findings compatible with aspiration. Radiological findings consistent with aspiration are relatively infrequent without preceding signs of regurgitation in resuscitated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…First, regurgitation and aspiration pneumonia occur commonly among adults successfully resuscitated from cardiac arrest and might also occur in chidlren. 7-9 Second, cardiac arrest may impair bowel wall barrier integrity as a result of ischemia-reperfusion injury leading to bacterial translocation and nosocomial infection. Third, cardiac arrest survivors usually need continued invasive mechanical ventilation and hemodynamic monitoring with arterial and venous catheters that increase their risk for hospital acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…First, regurgitation and aspiration pneumonia occur commonly among adults successfully resuscitated from cardiac arrest and might also occur in chidlren. 7-9 Second, cardiac arrest may impair bowel wall barrier integrity as a result of ischemia-reperfusion injury leading to bacterial translocation and nosocomial infection. Third, cardiac arrest survivors usually need continued invasive mechanical ventilation and hemodynamic monitoring with arterial and venous catheters that increase their risk for hospital acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…4,14 First of all, EOP after OHCA may be primarily considered to be a consequence of the combination of aspiration pneumonitis and aspiration pneumonia. 15,16 In fact, the distinction between these two entities is largely artificial, both being a continuum. 17 In the specific setting of cardiac arrest, they are both promoted by the loss of airway protection due to abrupt coma, mouth-to-mouth or bag ventilation, and chest compressions.…”
Section: Pathophysiology Risk Factors and Definitionmentioning
confidence: 98%
“…Regurgitation may occur in 12.4% of patients ventilated with BMV during OHCA while insertion of LMA may decrease this risk to 3.5% [50]. Another study showed an even higher incidence of this complication—20% of patients regurgitated at the scene and 24% of all resuscitated persons had radiological findings of aspiration on chest X-ray after admission to hospital [55]. All patients were intubated at the scene.…”
Section: Management During Resuscitationmentioning
confidence: 99%